An Ex-Post Assessment of RES-E Support in Greece by Investigating the Monetary Flows and the Causal Relationships in the Electricity Market - Vassilis Stavrakas; Nikos Kleanthis; Alexandros Flamos (Energies, 2020)
One way to perceive the electricity market is as a network of actors connected through transactions and monetary flows. By exploring the monetary flows in the electricity market, one adopts a holistic view which can provide insights on the interactions between different components of the benefits and costs, as well as on the possible conflicts or alliances between the involved actors of the system. The importance of such an analysis becomes even more evident when considering if the system’s state would change due to either the effectuation of a policy measure or a shift in the external drivers of the system. Additionally, by identifying conditions of conflicting interests between the involved actors, one can devise a roadmap of least-resistance for a policy measure to attain its goals. Our work is based on the premise that understanding and quantifying the monetary flows in the electricity market can contribute to the efficiency assessment of policy interventions in the market. We present a structured analytical framework and the results of a quantitative analysis, based on available public domain data, for the identification of the main drivers and interactions that governed the major monetary flows in the Greek wholesale electricity market, from 2009 to 2013 and the ex-post assessment of the market impact of the feed-in-tariffs scheme that was in place during this period.